CURVULARIA PULMONARY FUNGAL INFECTION ASSOCIATED WITH IMMUNOCOMPROMISED PATIENT: HOW CT SCAN COULD HELP IN MAKING DIAGNOSIS - Kristina Paskalita Kero; Dini Rachma Erawati (Department of Radiology, Medical Faculty, University of Brawijaya, 2023)
Pulmonary fungal infections can be found in immunocompetent and immunocompromised patients. The Curvularia species of fungi are rarely seen in humans. These fungi can be clinically significant and cause a range of disease processes, particularly in immunocompromised patients. We present a 24-year-old male patient diagnosed with SLE 5 years ago, complaining of fever five days before hospital administration concerning pneumonia. A CT scan revealed consolidation and multiple lung nodules compatible with a fungal pulmonary infection. The result of the sputum culture indicated Curvularia. A chest radiograph showed infiltrates with consolidation in the middle-lower lobes of both lungs. Early and second CT-scan findings revealed ground-glass opacity surrounding multiple irregular nodules (halo signs), cavitary nodules, and reverse halo signs. Afterward, the result of the patient’s sputum culture demonstrated fungal growth of the Curvularia species. The patient then underwent fungal treatment with fluconazole and voriconazole. The patient showed improvements, and a follow-up chest CT scan revealed the resolution of the lesion after fungal treatment. CT-scan examination, clinical condition, and microbiology culture can help diagnose Curvularia pulmonary fungal infection in immunocompromised patients. Keyword: Phaeohyphomycosis; Curvularia; Halo sign; Reverse halo sign